Clinical practice guide for the treatment of perforating dermatosis. Issue 12 (23rd October 2020) - Kawakami, Tamihiro; Akiyama, Masashi; Ishida‐Yamamoto, Akemi; Nakano, Hajime; Mitoma, Chikage; Yoneda, Kozo; Suga, Yasushi
Abstract: Perforating dermatoses are a heterogeneous skin disease group defined by transepidermal elimination of various skin materials. Four classical forms of primary perforating dermatosis have been described, where the transepidermal elimination mechanism represents the hallmark of the disease: acquired reactive perforating collagenosis, elastosis perforans serpiginosa, Kyrle's disease and perforating folliculitis. Acquired reactive perforating collagenosis presents with transepidermal elimination of collagen fibers. Elastosis perforans serpiginosum presents with the elimination of elastic fibers. Kyrle's disease presents with transepidermal elimination of abnormal keratin. In perforating folliculitis, it is the content of the follicle. We established diagnostic criteria and severity classification. In addition, the Japanese guideline for treatment of perforating dermatoses was updated using the Medical Information Network Distribution Service (MINDS) methodology. The guideline is based on a systematic published work review completed from 1989 to 2019, and on a formal consensus and approval process. Most medical published work on the treatment is limited to individual case reports and small series of patients. The guideline covers treatment options considered relevant by the expert panel and approved in Japan at the time of the consensus conference.